Impostor Phenomenon, Self-Esteem, and Self-Efficacy - Wulandari, Aprilia Dwi; Tjundjing, Sia (ANIMA Indonesian Psychological Journal, 2007)
This study aims to investigate whether the impostor phenomenon exists among students, and to expose its relation with self-esteem and self-efficacy. Subjects (N = 124) were obtained through purposive sampling towards psychology students. Data were collected through a questionnaire adapted from a standard scale. A descriptive statistical analysis was conducted, followed with a chi square test, and Pearson correlation. Results reveal that 29.8 % subjects are impostors. Data analysis show that it correlates negatively with self-esteem and self-efficacy. The impostor phenomenon as an entity interconnected with self-image fulfillment are discussed. Penelitian ini bertujuan memberikan gambaran mengenai impostor phenomenon pada mahasiswa, dan mengungkap keterkaitannya dengan self esteem dan self efficacy. Subjek penelitian (N = 124) diperoleh melalui purposive sampling terhadap mahasiswa psikologi. Data diperoleh melalui kuesioner yang diadaptasi dari skala baku. Analisis dengan teknik statistik deskriptif dilanjutkan dengan uji kai kuadrat, dan korelasi Pearson. Hasil penelitian menunjukkan bahwa 29,8 % subjek tergolong impostors. Analisis data menunjukkan bahwa impostor phenomenon berkorelasi negatif dengan self esteem dan self efficacy. Dibahas impostor phenomenon sebagai suatu fenomena terkait pemenuhan gambaran diri.